Calculation of Internal and External Pressures of Thick-Walled Pipes under the Influence of Aerial Flows (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
water reservoirs are designed with different radii and thicknesses of water discharge systems or engineering pipes in accordance with the water discharge effort. The thicknesses of the pipes in the drainage system are different for pipes working under high pressure.